(untitled) (Cadernos de Psicologia Social do Trabalho, 2013)
This study analyzed the psychosocial effects for the families of the victims of fatal work accidents occurred in thesector of marble and granite in 2008, in the state of Espírito Santo, Brazil. In the exploratory research, semistructuredinterviews were utilized as the means of collection of data, whose analysis followed the Method of SensesInterpretation. Eight families, identified through the Work Accidents Communication, participated in the research.The families’ perceptions about the work accidents were associated to the characteristics of the activity in the rocksector, such as: work conditions unfavorable to safety, proximity between personal and professional relations andlack of information about accidents. The fatal work accidents brought several implications for all the familymembers, for instance, damage to health, behavioral changes and difficulty to deal with the break of plans. Themanners of facing death indicated that the overcoming of losses was mainly enabled by family members, friends andreligion. Most of the companies complied with all the legal obligations with promptitude. Government washighlighted regarding the benefits granted to families of the victims; however, it was absent in the transformationalactions toward the organization of work in order to prevent accidents.